Pengaruh Pendapatan, Pengetahuan Dan Kerentanan Penyakit Terhadap Willingness To Pay (WTP) Premi Jaminan Kesehatan Pada Pekerja Sektor Informal - Dwi Prakoso, Anom (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2021)
Background: The Indonesian Government’s target of Universal Coverage or 100% Health Insurance participation by 2019 failed to be achieved, even until the end of October 2020. The failure of universal coverage resulted in BPJS Health’s finances getting worse after experiencing a deficit. Informal sector workers are the most dominant sector that has not participated in the Health Insurance scheme, totaling 30,487,891 workers. Low income, uncertain each month and the increase in contributions resulted in a decrease in Willingness to pay Health Insurance contributions. Research purposes: The purpose of this study is to analyze the effect of income, knowledge and disease susceptibility to the willingness to pay (WTP) of health insurance contributions to informal sector workers. Method: This cross-sectional research was conducted in Kudus Regency, Central Java in January-February 2020. Sampling used purposive sampling with a total of 200 informal sector workers who had not yet participated in BPJS Kesehatan. The dependent variable is willingness to pay. The independent variables are income, knowledge and disease susceptibility. Data collection using a questionnaire and data analysis with logistic regression. Result: Willingness To Pay health insurance contributions for informal sector workers increased in income ≥Rp 2,218,451 (b = 2.02; 95% CI = 1.01-3.55; p = 0.044), high knowledge (b = 4.64; 95% CI = 2.36-8.31; p <0.001), high disease susceptibility (b = 3.01; 95% CI = 0.26-5.75; p = 0.031). Conclusion: Income, knowledge and disease vulnerability have a significant effect on the willingness to pay of health insurance contributions for informal sector workers.